Strengthening Public Financial Accountability: A Legal Analysis of Nepal’s Budgetary and Expenditure Control Mechanisms - Bhandari, Sushma (Samsad Journal संसद जर्नल, 2026)
This paper provides a comprehensive legal analysis of Nepal's public financial management (PFM) system, focusing on budgetary and expenditure control mechanisms and their role in ensuring accountability. Nepal's constitutional framework establishes the Office of the Auditor General (OAG) as the central oversight institution, supported by Appropriation Acts and the Financial Procedure and Fiscal Accountability Act (FPFAA). However, implementation faces significant challenges including weak expenditure controls, inadequate cash planning, provincial capacity deficits, poor inter-agency coordination, and limited audit follow-up. This study has examined the legal and constitutional foundations of Nepal's PFM system, analyzes the effectiveness of existing control mechanisms, identifies challenges, and proposes recommendations. Key recommendations are clarifying legal mandates, enhancing cash management systems, strengthening OAG capacity and enforcement mechanisms, building provincial financial management capabilities, improving inter agency coordination, and increasing transparency with effective sanctions for non compliance. The analysis from scholarly sources examining Nepal's fiscal legal framework, budgetary practices, audit systems, and reform initiatives to provide evidence-based insights for policy makers and practitioners.